Sol-gel processing for advanced ceramics, a perspective - Plinio Innocenzi (Open Ceramics, 2023)
Sol-gel chemistry and the process that peculiarly defines the derived materials, represent an essential tool for the chemical synthesis of materials. Since the intensive research activity that began in the late 1980s, whole new families of advanced ceramic materials obtained via chemical synthesis combined with low-temperature heat treatment have been developed. These materials include, among others, aerogels, organic-inorganic hybrid materials, and mesoporous materials. The success of the process has thus opened up new possibilities for obtaining nanomaterials through a highly refined design of the structure and, thus, of the properties. Despite the intervening time, the sol-gel process is still the focus of intense research, and more and more new applications are successfully entering the market. This article is devoted to a brief review of the future prospects of the process and materials obtained through sol-gel chemistry.